PELATIHAN PENULISAN ARTIKEL UNTUK PUBLIKASI DI JURNAL ILMIAH UNTUK MENINGKATKAN PROFESIONALISME BAGI GURU-GURU DI KECAMATAN KUBUTAMBAHAN KABUPATEN BULELENG - ketut sedana arta (ACARYA PUSTAKA, 2018)
PELATIHAN PENULISAN ARTIKEL UNTUK PUBLIKASI DI JURNAL ILMIAHUNTUK MENINGKATKAN PROFESIONALISME BAGI GURU-GURU DIKECAMATAN KUBUTAMBAHAN KABUPATEN BULELENGOlehKetut Sedana ArtaJurusan Pendidikan SejarahABSTRACTThe main objectives of the Community Service activities are: (1) Enhancing thedevelopment of teachers' professionalism in the context of promotion requirements, (2)Improving the ability of teachers to compile and present scientific papers, (3) Produceproducts of scientific work that are ready to be published in scientific journalsThe results obtained from all stages of the P2M implementation activities can be detailed asfollows: teachers at every level the ability to write scientific articles is still lacking. Someobservations and interviews with teachers provide clarity as to why teachers have not beenable, willing, and used to writing science. The causes of the low ability of teachers in writingscientific papers, namely: (1) lack of knowledge, understanding, and skills of teachers inwriting scientific papers, especially writing scientific articles, (2) limited scientific readingfacilities, especially in the form of scientific magazines or journals, (3) the unavailability ofmagazines or journals in the school or district education office that can accommodate thewritings of the teachers, (4) the limited implementation of scientific writing competitions heldby the education office at the national, provincial and district levels, and (5) the lowmotivation of teachers to take part in scientific writing competitions. In connection with this,there are several strategies offered, one of them is by conducting article training forpublication in a journal. After being given training by a team of experts from UndikshaSingaraja, elementary school teachers can begin to compile and package articles.Keywords: write, articles, published, scientific, journals